Induction of Matrix Metalloproteinases in Chondrocytes by Interleukin IL-1Î² as an Osteoarthritis Model - Ervi Afifah; Tjandrawati Mozef; Ferry Sandra; Seila Arumwardana; Dwi Davidson Rihibiha; Hayatun Nufus; Rizal Rizal; Annisa Amalia; Indra Bachtiar; Harry Murti; Wahyu Widowati (Journal of Mathematical and Fundamental Sciences, 2019)
Osteoarthritis (OA) is a chronic disease of the joints and bones due to trauma or other joint-related diseases (secondary). Synovial inflammation commonly causes disturbance in joint homeostasis, which is associated with OA. Enzymes such as aggrecanase and metalloproteinase generate cartilage damage, mediated by tumor necrosis factor (TNF-Î±) and interleukin (IL)-1. Pro-inflammatory cytokines, including TNF-Î±, IL-1Î², and IL-6, are responsible for regulation of the extracellular matrix, cartilage degradation, and apoptosis of chondrocytes. This study aimed to observe the cell viability and expression level of matrix metalloproteinases (MMP-1 and MMP-3) and tissue inhibitor metalloproteinases (TIMP-1 and TIMP-2) in human chondrocyte cells (CHON-002) induced by IL-1Î². CHON-002 was induced with IL-1Î² (0.1, 1 and 10 ng/mL) as an OA model. The viability of the cells was measured with a 3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxyme-thoxyphenyl)-2-(4-sulfophenyl)-2H-tetra zolium (MTS) assay, while expression of MMP-1, MMP-3, TIMP-1, and TIMP-2, was evaluated by RT-PCR. The viability of IL-1Î²-induced CHON-002 (CHON-002- IL-1Î²) cells at day 1 and 5 showed that treatment with up to 10 ng/mL of IL-1Î² was not toxic. Expression of TIMP-1 and TIMP-2 in CHON-002-IL-1Î² was lower compared to control, while that of MMP-1 and MMP-3 was higher compared to control. These results indicate that CHON-002 treated with 10 ng/mL IL-1Î² has expression patterns consistent with chondrocyte damage, so the CHON-002-IL-1Î² system may serve as a model for MMP induction in OA.